Understanding multimodal representations of junior high school students when writing scientific explanations - I Budiman; I Kaniawati; D Rusdiana (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This research is an attempt to analyze the understanding of the concept of staticelectricity in junior high school students expressed in the form of scientific explanatory textfrom the linguistic point of view, for the development of multimodal representationcompetence. Scientific explanations in the form of text made by 9th-grade junior high schoolstudents through worksheets in static electricity studies provided by experienced scienceteachers are data from this study. The text created by the learner is analyzed by examininglexicogrammar through a systemic framework analysis of Systemic Functional Linguistic (SFL). Our analysis identifies specific aspects of the language that students need to beappropriate in expressing an understanding of static electricity that is aligned with the scientificperspective and competence of multimodal representation of students from the teacher-createdworksheet. The findings of this study indicate that conceptual understanding is not sufficient todevelop multimodal representations competence. The implications of this research are expectedto assist teachers in overcoming linguistic challenges in explaining static electricity anddeveloping multimodal representations competence.